EVIDENCE OF ABNORMAL LEFT VENTRICULAR FUNCTION IN PATIENTS WITH THALASSAEMIA MAJOR: AN ECHOCARDIOGRAPHY BASED STUDY - Arshad, Muhammad Sohail; Hyder, Syed Najam (Journal of Ayub Medical College Abbottabad, 2009)
Background: Thalassaemia represent one of the most common single gene disorder causing a major public health problem in Pakistan. Nearly 100,000 people are born worldwide with this severe blood disorder every year. Over the last 3 decades, the development of regular transfusion therapy and iron chelation has dramatically improved the quality of life and transformed thalassaemia from a rapidly fatal disease to a chronic disease compatible with prolonged survival. Objective of this observational cross sectional study was to determine the effects of chronic anaemia and transfusional iron overload on the left ventricular function using Doppler echocardiography. Methods: This study was conducted in the Department of Paediatric Cardiology, The Children's Hospital & Institute of Child Health, Lahore, Pakistan from 1st April 2006 to 30th September 2007. The study comprised of 50 consecutive cases of beta-Thalassaemia major and 30 controls with normal haemoglobin and electrophoresis pattern. Î²- Thalassaemia major patients were diagnosed on the basis of haemoglobin electrophoresis. Patients with any congenital or acquired heart disease, concurrent infective disorder and with history of cardiac surgery were excluded from the study. 2-D, M-mode and Doppler echocardiography was performed in all the study cases and controls. Statistical comparison of study cases and controls was conducted by using unpaired t-test. Results: The age of the patients ranged from 2 years to 25 years with mean age of 9.65 years. Males were 34 (68%) and females were 16 (32%). None of the study cases was on regular chelation programme while 31 (62%) patients were on irregular chelation with single dose of intravenous desferrioxamine only at the time of blood transfusion. 19 (38%) of the patients had LV dysfunction in the form of isolated systolic dysfunction in 2 (4%), isolated diastolic dysfunction in 15 (30%) while global dysfunction in 2 (4%) of the patients. Left ventricular dimensions, stroke volume and E/A ratio were found considerably high in the study group. Conclusion: A very high percentage of Thalassaemia patients have cardiac involvement as LV dysfunction. This is mainly due to chronic anaemia, poor compliance with chelation therapy and non-availability of proper cardiac monitoring. Regular assessment of cardiac function may help a lot to improve the quality of life of these patients and may reduce the morbidity and mortality to a great extent. Keywords: Beta Thalassaemia major, Echocardiography, Left ventricular dysfunction